Application of the Problem Based Learning Model to Improve Students' Learning Outcomes and Critical Thinking Ability on Mathematics Lessons in Primary School - Tanjung, Darinda Sofia; Ambarwati, Nova Florentina; Juliana, Juliana; Prayuda, Meikardo Samuel (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
This research was conducted at SDN 06402 Medan Tuntungan with the aim of improving critical thinking skills and student learning outcomes in mathematics subjects by using the Problem Based Learning learning model for fifth grade students at SDN 06402 Medan Tuntungan for the 2023/2024 academic year. This research is Classroom Action Research. implemented in two cycles. The subjects in this research were 30 class V students consisting of 13 female students and 17 male students. The data collection techniques used are observation and tests. The results of this research indicate that there is an increase in students' critical thinking abilities and student learning outcomes. This can be seen from the increase in students' critical thinking, namely in cycle I there were 12 students who got a pass mark or 40%, while 18 students who did not complete it or 60%. So, the second cycle of research was continued, namely 26 students who got a pass mark or 87%, while 4 students who did not get a pass mark or 13%, then there was an increase in cycle II compared to cycle I and they had fulfilled the predetermined completion. Thus, it can be concluded that using the Problem Based Learning learning model in mathematics lessons in class V of SDN 064025 Medan Tuntungan 2023/2024 can improve critical thinking abilities and student learning outcomes.